Incidences of the improvement of the interactions between MAC and routing protocols on MANET performance - Hamrioui, Sofiane; Daoui, Mehammed; Chamek, Linda; Lalam, Mustapha; Lorenz, Pascal (Journal of Advanced Computer Science & Technology, 2012)
In this paper, we present an improvement for the interactions between MAC and routing protocols to better energy consumption in MANET (Mobile Ad hoc Networks) and show its incidences on the performance of the network. We propose a new approach called IMR-EE (Improvement of the Interactions between MAC and Routing protocol for Energy Efficient) which exploits tow communication environment parameters. The first one is the number of nodes; our approach reduces the additional energy used to transmit the lost data by making the size of the backoff interval of MAC protocol adaptable to the nodes number in the network. The second parameter is the mobility of nodes; IMR-EE uses also the mobility of nodes to calculate a fairness threshold in order to guarantee the same level of the residual energy for each node in the network. We evaluate our IMR-EE solution with NS (Networks Simulator) and study its incidences on data lost and energy consumption in the network under varied network conditions such as load and mobility. The results showed that IMR-EE outperform MAC standard and allows significant energy saving and an increase in average lifetime of a mobiles nodes in the network.